Intervensi Perilaku dan Aktivitas Fisik pada Pasien Gangguan Bipolar dengan Obesitas dan Emotional Eating: Laporan Kasus - Meidian Sari; Abdullah Sahab; Lilis Khairani; Ahmad Ghiffari; Raden Ayu Tanzila (Lembaga Pengembangan Kinerja Dosen, 2026)
Obesity is a growing global health problem. Obesity is more common among patients with bipolar disorder than in the general population and has been associated with greater clinical burden, including depressive symptoms, impaired functioning, poorer quality of life, and metabolic complications. Case Presentation: A 38-year-old woman with a five-year history of bipolar III disorder presented with a 15 kg weight gain over two years. She had a history of manic episodes followed by depressive episodes. During depressive phases, she reported fatigue, low motivation, emotional eating, increased appetite, and preference for high-carbohydrate foods. She had been treated with valproate 750 mg/day and olanzapine 10 mg/day. Management included pharmacotherapy review, switching olanzapine to lurasidone due to lower metabolic risk, nutritional counselling, structured physical activity, cognitive behavioral strategies for emotional eating, sleep routine education, and family support. Conclusion: Behavioral intervention combined with regular physical activity may be a relevant adjunctive approach for patients with bipolar disorder, obesity, and emotional eating. This case highlights the need to assess eating behavior, sleep routine, physical activity, metabolic risk, and adaptive coping strategies in patients with bipolar disorder and obesity.